2007
DOI: 10.1007/s10832-007-9086-6
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Bi4Ti3O12 and Bi4−x La x Ti3O12 ceramics prepared by a new sol-gel route

Abstract: Ceramics of bismuth titanate, Bi 4 Ti 3 O 12 (BIT) and the La-doped series, Bi 4−x La x Ti 3 O 12 (xBLT) with x= 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, and 0.75, have been synthesized by a new sol-gel process based on ethylene glycol. La-doping is found to reduce the temperature of the formation of pure Bi-layer-structured phase from 600°C in BIT and low La-doped xBLT (x=0.1-0.3) to 500°C in high La-doped xBLT (x=0.4-0.75). Increasing the La-content in the xBLT ceramics decreases the contribution of the space char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The mixture at practically atomic level favors the reaction to synthesize precursors at low temperatures, allowing the control of particle size and shape. Thus, different compositions with Aurivillius-type structure were synthesized, at temperatures that can range from 525 to 700 • C [12][13][14][15][16] [24]. In other cases, the synthesis temperature is decreased by obtaining an amorphous powder after milling [25][26][27].…”
Section: Processing Of Ceramics With Aurivillius Type Structurementioning
confidence: 99%
“…The mixture at practically atomic level favors the reaction to synthesize precursors at low temperatures, allowing the control of particle size and shape. Thus, different compositions with Aurivillius-type structure were synthesized, at temperatures that can range from 525 to 700 • C [12][13][14][15][16] [24]. In other cases, the synthesis temperature is decreased by obtaining an amorphous powder after milling [25][26][27].…”
Section: Processing Of Ceramics With Aurivillius Type Structurementioning
confidence: 99%
“…Curie Among the all ceramic samples, maximum ɛ r of 5812 was observed for x = 0.60, at T c of 520 0 C. It was also observed that BLT samples compared with our previously reported BT (x = 0) ceramics [10] possess a higher  r indicating that La plays an important role in the electrical properties of the BT layers. Doping BT with La has a strong influence on the dielectric behavior of the material even at low and high concentration [13].…”
Section: Electrical Analysismentioning
confidence: 99%
“…At present, there are two main ways to solve the above problems and modify the properties of the BIT ceramics. One is modification through component design, such as doping substitution at the A or B-site [14,15]. Element doping is an effective modification method that can significantly affect the microstructure and improve piezoelectric and ferroelectric properties [16−18]; the other is modification through preparation processes, such as the molten salt method [19].…”
mentioning
confidence: 99%
“…Element doping is an effective modification method that can significantly affect the microstructure and improve piezoelectric and ferroelectric properties [16−18]; the other is modification through preparation processes, such as the molten salt method [19]. The B-site modification is one of the most effective modification methods, which introduces high-valence cations such as Nb 5+ , W 6+ , and Ta 5+ [14,20,21] or co-doped cations such as Zn 2+ /Nb 5+ , Cu 2+ /Nb 5+ , and Cu 2+ /Ta 5+ [22−24] into the B-site of BIT to enhance piezoelectric activity. Furthermore, some studies indicate that non-equivalent doping, where high-valence ions replace low-valence ones, can inhibit the formation of oxygen vacancies and thus enhance electrical resistivity at high temperatures [25].…”
mentioning
confidence: 99%